CD36 and Its Role in Regulating the Tumor Microenvironment - Xinzhi Liao; Sheng Yan; Jialin Li; Chengming Jiang; Sigen Huang; Shengyin Liu; Xiaofeng Zou; Guoxi Zhang; Junrong Zou; Quanliang Liu (Current Oncology, 2022)
CD36 is a transmembrane glycoprotein that binds to a wide range of ligands, including fatty acids (FAs), cholesterol, thrombospondin-1 (TSP-1) and thrombospondin-2 (TSP-2), and plays an important role in lipid metabolism, immune response, and angiogenesis. Recent studies have highlighted the role of CD36 in mediating lipid uptake by tumor-associated immune cells and in promoting tumor cell progression. In cancer-associated fibroblasts (CAFs), CD36 regulates lipid uptake and matrix protein production to promote tumor proliferation. In addition, CD36 can promote tumor cell adhesion to the extracellular matrix (ECM) and induce epithelial mesenchymal transition (EMT). In terms of tumor angiogenesis, CD36 binding to TSP-1 and TSP-2 can both inhibit tumor angiogenesis and promote tumor migration and invasion. CD36 can promote tumor angiogenesis through vascular mimicry (VM). Overall, we found that CD36 exhibits diverse functions in tumors. Here, we summarize the recent research findings highlighting the novel roles of CD36 in the context of tumors.